Analysis of Productivity and Income of Floating Net Cage Businesses in the Koto Panjang Hydroelectric Reservoir, Riau - Putri, Afrina; Darwis, Darwis; Yanti, Chicka Willy (Jurnal Perikanan dan Kelautan, 2025)
The development of fish farming in floating net cages (KJA) in the Koto Panjang Hydroelectric Power Plant Reservoir is a strategic alternative to overcome the limitations of capture fisheries production. This study aims to analyze the productivity and income of KJA businesses based on business scale (small, medium, and large). The study was conducted from September to August 2024 at the Koto Panjang Hydroelectric Power Plant Reservoir, Riau Province. The research method involved a survey with primary data collection through interviews using questionnaires and secondary data from supporting literature. Data analysis included total productivity, gross income, net profit, production costs, and the income-to-cost ratio (R/C). The study results indicate that business productivity increases with scale, with an R/C ratio of 1.52 for small-scale businesses, 1.68 for medium-scale businesses, and 1.73 for large-scale businesses. Business income and profits also show significant increases at larger business scales. The average profit per period for small-scale businesses was IDR 331,771,000, for medium-scale businesses IDR 1,341,124,000, and for large-scale businesses IDR 6,472,092,000. An R/C ratio greater than one indicates that all scales of KJA businesses at the Koto Panjang PLTA Reservoir are economically profitable. This study recommends increasing the utilization of water resources and information technology to enhance efficiency and increase the income of fish farmers